Can fostering posttraumatic growth prevent burnout and promote resilience in future nurses? - Sim, Jae-Chang; Lee, Dayoung; Park, Jubeen; Im, Sun-Young (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to develop and validate a psychological support program incorporating psychological factors that promote PTG, in order to prevent burnout and enhancing resilience in future healthcare workers in preparation for infectious disease outbreaks such as the COVID-19 pandemic. The program was developed with consideration to the characteristics of nurses. Since nurses, particularly, suffered from severe burnout during the COVID-19 pandemic, the efficacy in this study was tested in nursing trainees.MethodBased on a review of related literature, we developed a program consisting of eight sessions. The content of the program includes physical and emotional recognition, finding meaning in stressful events, understanding and reflection on posttraumatic growth (PTG), promoting happiness and finding value, and inspiring hope. To test the effects of the program, participants were divided into control and intervention groups. PTG, resilience, burnout, emotion processing, deliberate rumination, and mental wellbeing were measured pre-intervention, post-intervention, and at later follow-up.ResultsUsing a repeated-measures analysis of variance, the treatment group showed increased PTG, resilience, mental wellbeing, and emotion processing after the intervention compared with the control group, and this increase was maintained in the follow-up. Although the effect on burnout was not statistically significant, there was a trend for relatively decreased burnout in the treatment group.ConclusionThese results demonstrate the potential effectiveness of psychological program in promoting healing and growth to support healthcare workers’ mental health. By fostering PTG and resilience, the program offers practical benefits for preventing future stress and burnout in healthcare settings.